Penatalaksanaan Fisioterapi Pada Kasus Carpal Tunnel Syndrome Sinistra Di RSUD Soehadi Prijonegoro Sragen - Rahim, Amalia Faradilla, Dwi Kurniawati, SSt.FT.,M.Kes (2016)
Background: Carpal tunnel syndrome is an injury caused by entrapment of the median nerve in carpal tunnel. It is characterized by the onset of pain, numbness, or tingling in the area which innervated by the median nerve. Disorders that arise in the CTS is caused by excessive use of hands to repeated stress, the twist of the wrist, fracture colles, etc. Objective: To investigate the implementation of physiotherapy in reducing pain, increasing muscle strength, increasing range of motion and functional activity of the left hand on CTS , using modalities ultrasound, nerve mobilitation, and tendon gliding. Result: After treatment for 6 times, the obtained results for static pain is T0 : 2 to T6 : 0, motion pain T0 : 6 to T6 : 3, press pain T0 : 4 to T6 : 2, increasing range of motion T0 S: 60º - 0º - 55° to T6 S: 65-0-60 and T0 F : 20°-0°-30°, to T6 F: 25°-0°-35°. increasing muscle strenght flexor wrist T0 : 4 to T6 : 5,ekstensor wrist T0 : 4 to T6 : 5,radial deviasi T0 : 5 to T6 : 5, ulnar deviasi T0 : 5 to T6 : 5, wrist and hand disability index T0 : 17 point to T6 : 12 point. Conclusion : Ultra Sound (US) , nerve mobilitation, and tendon gliding can reducing pain, increasing muscle strength, increasing range of motion and functional activities of CTS (carpal tunnel syndrome) problems. Keyword : Carpal tunnel syndrome(CTS), ultra Sound (US), ULTT 1, tendon gliding, wrist and hand disability (WAHDI).